Serious Games Supported by Virtual Reality—Literature Review - Nadia Damianova; Santiago Berrezueta-Guzman (IEEE Access)
Serious games supported by virtual reality (VR) offer innovative solutions across diverse fields, such as education, therapy, and professional training, leveraging immersive and interactive environments to enhance engagement and learning outcomes. This paper provides a comprehensive literature review of VR-based serious games, focusing on their applications, benefits, and challenges. Key themes include the transformative impact of VR on education through improved motivation and experiential learning, therapeutic applications addressing physical and mental health, and professional training in hazardous and high-skill environments. Despite their potential, adoption is hindered by challenges such as high costs, limited accessibility, ethical concerns, and technical limitations, including cybersickness and scalability issues. This review also highlights emerging trends, including AI-driven adaptive learning, advancements in haptic feedback, and the integration of multisensory experiences, offering opportunities to address these barriers. By synthesizing current research and identifying critical gaps, this paper provides actionable recommendations for researchers and developers to maximize the impact of serious VR games in creating inclusive, effective, and scalable solutions for diverse user needs.